2020
DOI: 10.1558/cj.38777
|View full text |Cite
|
Sign up to set email alerts
|

Researching Identity and L2 Pragmatics in Digital Stories

Abstract: This study explores college EFL learners' construction of identity through the analysis of their pragmatic choices in digital stories, in which they narrated their relationship with another person they had helped in the past. More specifically, such choices were examined following Relational Dialectics Theory in learners' enactments of "connection" with and "autonomy" from this person. A specific view of identity in language education, the notion of "relational work" in (im)politeness research, and a social se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Online practice activities develop professional identity through the use of modes such as forums and blogs (Farr & Riordan, 2015). Kim et al (2021) reported the efficacy of digital stories in developing language teachers’ professional identities by interacting and narrating pragmatic choices and selecting semiotic resources (García‐Pastor, 2020). Online collaboration not only develops teachers’ digital literacy but also promotes professional interactions and influences teacher identity development (Kitade, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Online practice activities develop professional identity through the use of modes such as forums and blogs (Farr & Riordan, 2015). Kim et al (2021) reported the efficacy of digital stories in developing language teachers’ professional identities by interacting and narrating pragmatic choices and selecting semiotic resources (García‐Pastor, 2020). Online collaboration not only develops teachers’ digital literacy but also promotes professional interactions and influences teacher identity development (Kitade, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Second, the data that represented TALL research data were divided into four subcategories (reported affordances, reported challenges, adopted data collection method, adopted theoretical framework/perspective in keeping with Bahari, (2020) and Bahari et al, (2021b) in response to eight research questions (see Table 1). These subcategories informed about the affordances and challenges that were identified and reported either by teachers or researchers.…”
Section: Methodsmentioning
confidence: 99%
“…Dooly & Tudini, 2016), Spanish as a FL (e.g. García-Pastor, 2020), German as FL (e.g. Cunningham & Vyatkina, 2012), Japanese as a FL (e.g.…”
Section: Tech-mediated Tasks For L2 Pragmaticsmentioning
confidence: 99%
“…The majority of studies point out that L2 learners are competent users of technology-mediated spaces and they deploy a variety of interactional norms, semiotic resources, and politeness strategies to maintain communication (Cunningham & Vyatkina, 2012; Gonzales, 2013; Tercedor Cabrero, 2013) and they are able to craft positive identities for themselves (García-Pastor, 2020).…”
Section: Tech-mediated Tasks For L2 Pragmaticsmentioning
confidence: 99%